2017
DOI: 10.1530/jme-17-0042
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic islet inflammation: an emerging role for chemokines

Abstract: Both Type 1 and Type 2 diabetes exhibit features of inflammation associated with alterations in pancreatic islet function and mass. These immunological disruptions, if unresolved, contribute to the overall pathogenesis of disease onset. This review presents the emerging role of pancreatic islet chemokine production as a critical factor regulating immune cell entry into pancreatic tissue as well as an important facilitator of changes in tissue resident leukocyte activity. Signaling through two specific chemokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 150 publications
(183 reference statements)
1
29
0
Order By: Relevance
“…In particular, the proinflammatory chemokine CXCL10 seems to be directly induced by acquisition of a senescent phenotype and is involved in the recruitment of autoreactive T‐lymphocytes in pancreatic islets, thus contributing to insulitis and β‐cell destruction. In accordance to these results, previous studies showed that CXCL10 is expressed in islet endocrine cells of T1D donors and plays a critical role in disease pathophysiology . Roep et al observed that the elevated levels of this chemokine in islets of recent‐onset T1D donors corresponded with the juxtaposed infiltration of lymphocytes bearing its cognate receptor CXCR3; of note, both CXCL10 + endocrine cells and CXCR3 + lymphocytes were undetectable in pancreas of non‐diabetic control donors .…”
Section: β‐Cell and α‐Cell Responses To Islet Inflammation In T1dsupporting
confidence: 77%
“…In particular, the proinflammatory chemokine CXCL10 seems to be directly induced by acquisition of a senescent phenotype and is involved in the recruitment of autoreactive T‐lymphocytes in pancreatic islets, thus contributing to insulitis and β‐cell destruction. In accordance to these results, previous studies showed that CXCL10 is expressed in islet endocrine cells of T1D donors and plays a critical role in disease pathophysiology . Roep et al observed that the elevated levels of this chemokine in islets of recent‐onset T1D donors corresponded with the juxtaposed infiltration of lymphocytes bearing its cognate receptor CXCR3; of note, both CXCL10 + endocrine cells and CXCR3 + lymphocytes were undetectable in pancreas of non‐diabetic control donors .…”
Section: β‐Cell and α‐Cell Responses To Islet Inflammation In T1dsupporting
confidence: 77%
“…If true, this would explain why therapies targeting the IL-1 signaling pathway have shown either mixed results or limited efficacy during clinical trials. Indeed, macrophages and β-cells clearly have a symbiotic relationship, with macrophages responding to ATP release from β-cells and β-cells responding to cytokines produced and secreted by macrophages [54] , [55] .…”
Section: Discussionmentioning
confidence: 99%
“…However, such inflammatory response is unlikely in our system with isolated islets. Instead, chemokines may interact with numerous chemokine receptors expressed on human islets and, in such way, trigger pathway signalling [ 36 , 37 ]. The mechanism of chemokine-induced signalling and its effect on insulin secretion is poorly investigated [ 38 ].…”
Section: Discussionmentioning
confidence: 99%